A Qualitative Study of Patients' Attitudes toward HIV Testing in the Dental Setting. (16th February 2012) - VanDevanter, Nancy; Combellick, Joan; Hutchinson, M. Katherine; Phelan, Joan; Malamud, Daniel; Shelley, Donna
Abstract : An estimated 1.1 million people in the USA are living with HIV/AIDS. Nearly 200, 000 of these individuals do not know that they are infected. In 2006, the CDC recommended that all healthcare providers routinely offer HIV screening to adolescent and adult patients. Nurse-dentist collaborations present unique opportunities to provide rapid oral HIV screening to patients in dental clinic settings and reach the many adults who lack primary medical providers. However, little is known about the feasibility and acceptability of this type of innovative practice. Thus, elicitation research was undertaken with dental providers, students, and patients. This paper reports the results of qualitative interviews with 19 adults attending a university-based dental clinic in New York City. Overall, patients held very positive attitudes and beliefs toward HIV screening in dental sites and identified important factors that should be incorporated into the design of nurse-dentist collaborative HIV screening programs.